ANALISIS AL-QU’RAN SURAH AT-TAHRIM AYAT 6 SEBAGAI PARADIGMA KELUARGA ISLAMI DALAM MEMBENTUK AKHLAK GENERASI ALPHA - Sari, Khovifah Puspita; Razzaq, Abdur; Imron, Kristina; Sari, Khovifah (STAI Syubbanul Wathon Magelang, 2025)
The rapid advancement of technology has significantly influenced parenting styles and the behavior or morality (akhlak) of children, especially among Generation Alpha—those born between 2010 and 2025 who grow up in an era where information is instantly accessible. This development presents both opportunities and challenges, particularly the threat of moral degradation caused by exposure to negative content. Islam, as a religion that promotes peace, emphasizes that the family serves as the first school for children, with parents as their primary educators. Surah At-Tahrim verse 6 explains that believers have the responsibility to protect themselves and their families from the torment of Hellfire. When connected to Islamic family education, this implies that parental responsibility and supervision encompass not only worldly matters but also spiritual (ukhrawi) dimensions. This study employs a qualitative method with a library research approach. The findings indicate that the spiritual responsibility of parents as role models remains relevant in the digital era, serving as digital mentors who can apply Qur’anic values as foundational principles.